2014
DOI: 10.1590/1983-084x/12_002
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação fitoquímica e atividade antioxidan e, antimutagênica e toxicológica do extrato aquoso das folhas de Ocimum gratissimum L.

Abstract: RESUMO:A espécie Ocimum gratissimum L., popularmente conhecida como alfavaca, é uma planta muito usada na medicina tradicional brasileira, à qual são atribuídas diversas atividades terapêuticas quando usada na forma de infuso de suas folhas. Neste estudo foi realizada a caracterização fitoquímica, a avaliação da ação antioxidante e a investigação dos efeitos antimutagênico e antigenotóxico, além do efeito mutagênico e genotóxico potencial do extrato aquoso liofilizado a parir das folhas de O. gratissimum (EAOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Its antinociceptive, intestinal motility antagonistic, antibacterial, and antifungal activities have been proven in previous study (Gontijo et al, 2014).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Its antinociceptive, intestinal motility antagonistic, antibacterial, and antifungal activities have been proven in previous study (Gontijo et al, 2014).…”
Section: Introductionmentioning
confidence: 69%
“…In addition to EO, the plant also produces saponins, flavonoids, tannins, and cardiac glycosides, as products of their secondary metabolism (Gontijo et al, 2014). Recent studies have demonstrated that clove basil EO has inhibitory effect on the growth of some fungi such as Penicillium and Rhizoctonia (Philippe et al, 2012;Sethi et al, 2013;Rizvi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For Silva et al (2012), the concentration of total phenols, demonstrated a significant result, measured in mg of gallic acid equivalent per gram of sample with 323.95 having +/-1.36 standard deviation, whereas in Kanumfre et al (2017) the value obtained for the species Croton antisyphiliticus Martius was 113.9 ± 1.49 (mg EAG/g), both respectively lower than the present study. In studies on plant extracts, there are statistical correlations between the content of total polyphenols measured by the Folin-Ciocalteu method and antioxidant activity determined by the DPPH test, showing the importance of these secondary metabolites for antioxidant activity (Gontijo et al, 2014).…”
Section: Phenolics Compounds Determinationmentioning
confidence: 99%
“…This finding fits in the red propolis analyzed in this study since in the evaluation of the chemical composition of the extract, high levels of phenolic compounds and flavonoids, and high antioxidant activity was found. Phenolic compounds have been reported to have genoprotective activity because of their antioxidant activity (Gontijo et al 2014). Thus, the antioxidant activity of red propolis could be the possible explanation for genoprotective effect.…”
Section: Genoprotective Effectmentioning
confidence: 99%